God of Promise and Voucher: Alienation, Reconciliation, and Resurrection - Moser, Paul K. (New blackfriars, 2024)
A Christian approach to suffering, sin, and evil cannot offer now a full theodicy. We now ‘know in part’ only regarding divine purposes in allowing suffering, sin, and evil. We can clarify instead how God interacts in righteousness with people as their God of promise and voucher in the midst of suffering, sin, and evil. To that end, this article illuminates a divine effort toward human reconciliation with God in righteousness and resurrection, despite our gaps in explaining suffering, sin, and evil. It identifies current reconciliation with God and resurrection by God that do not fully explain suffering, sin, and evil, but can be a voucher now in human experience and life for eventual eschatological reparations promised by God. If the Spirit of God can be such a voucher, so also can the reconciliation and resurrection now empowered by that Spirit. This article recognizes a special role for the divine ‘fruit of the Spirit’ identified by Paul. It also explains how this role figures in spiritual resurrection with Christ now, in advance of any resurrection of the body. The article contends that the spiritual resurrection in question emerges through reconciliation with God now in volitional cooperation with God’s unique moral personality traits.